Autologous Breast Reconstruction: Preoperative Magnetic Resonance Angiography for Perforator Flap Vessel Mapping - Agrawal, Mukta D.; Thimmappa, Nanda Deepa; Vasile, Julie V.; Levine, Joshua L.; Allen, Robert J.; Greenspun, David T.; Ahn, Christina Y.; Chen, Constance M.; Hedgire, Sandeep S.; Prince, Martin R. (Journal of Reconstructive Microsurgery, 2015)
Background Selection of a vascular pedicle for autologous breast reconstruction is time consuming and depends on visual evaluation during the surgery. Preoperative imaging of donor site for mapping the perforator artery anatomy greatly improves the efficiency of perforator selection and significantly reduces the operative time. In this article, we present our experience with magnetic resonance angiography (MRA) for perforator vessel mapping including MRA technique and interpretation.Methods We have performed over 400 MRA examinations from August 2008 to August 2013 at our institution for preoperative imaging of donor site for mapping the perforator vessel anatomy. Using our optimized imaging protocol with blood pool magnetic resonance imaging contrast agents, multiple donor sites can be imaged in a single MRA examination. Following imaging using the postprocessing and reporting tool, we estimated incidence of commonly used perforators for autologous breast reconstruction.Results In our practice, anterior abdominal wall tissue is the most commonly used donor site for perforator flap breast reconstruction and deep inferior epigastric artery perforators are the most commonly used vascular pedicle. A thigh flap, based on the profunda femoral artery perforator has become the second most used flap at our institution. In addition, MRA imaging also showed evidence of metastatic disease in 4% of our patient subset.Conclusion Our MRA technique allows the surgeons to confidently assess multiple donor sites for the best perforator and flap design. In conclusion, a well-performed MRA with specific postprocessing provides an accurate method for mapping perforator vessel, at the same time avoiding ionizing radiation.
Keywords: MRA; blood pool contrast agent; perforator flap artery imaging